2022
DOI: 10.1111/cid.13102
|View full text |Cite
|
Sign up to set email alerts
|

Implications of considering peri‐implant bone loss a disease, a narrative review

Abstract: Background Peri‐implantitis has been suggested to cause significant increasing proportions of implant failure with increasing time. Purpose To assess whether implant failure rates in long term studies are matching the supposed high prevalence of peri‐implantitis. Material and Methods This paper is written as a narrative review of the long‐term clinical investigations available in the literature. Results Some implant systems have seen unacceptable marginal bone loss figures with time coupled to increased implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 97 publications
3
24
0
Order By: Relevance
“…However, the authors did not point out the corticalization. Similarly, this is seen in Figure 5 in Albrektsson’s publication [ 93 ]. Today, the phenomenon of bone density increase can be analyzed qualitatively and, of course, in relation to the MBL [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 63%
“…However, the authors did not point out the corticalization. Similarly, this is seen in Figure 5 in Albrektsson’s publication [ 93 ]. Today, the phenomenon of bone density increase can be analyzed qualitatively and, of course, in relation to the MBL [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 63%
“…Data regarding implant systems and implant surface characteristics were not presented in this study due to the wide variety of systems from various companies. A recent review revealed good long-term survival rates independent of implant surface and roughness [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain genetic predispositions to peri-implantitis, such as tumor necrosis factor-alpha (TNF-⍺) or interleukin-1 (IL-1) polymorphisms, showed potential links in the onset of peri-implant diseases [ 35 , 36 , 37 ], although clear genetic patterns are still to be determined. In addition, immune-centered therapeutic approaches to improve osseointegration and prevent bone loss around implants were recently proposed in a review by Albrektsson et al, who emphasized the role of foreign body reaction and host response in the development of peri-implantitis [ 34 ]. These may account for the small percentage of patients with no clear risk factors identified in the present review.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Albrektsson et al proposed that personalized dental implant therapy and its implantogenomics concept may accelerate the development of genetic diagnostic tests as a target future therapeutic for residual ridge resorption (RRR) in elderly [16,93]. In this regard, it should be mentioned that the application of personalized dental medicine to the realm of dental implant requires innovative leadership to direct wide-spectrum of scientific and clinical research as well as multidisciplinary and multicenter collaborations.…”
Section: Personalized Dental Implant Therapy: Introducing Implantogen...mentioning
confidence: 99%